Influence of organic and inorganic sources of nutrients on growth, yield and quality of mungbean (Vigna radiata) - MEENA, RAM SWAROOP; VERMA, TARUN; VERMA, SUNIL KUMAR; SINGH, AJEET; KUMAR, SUNIL; GURJAR, D S (The Indian Journal of Agricultural Sciences, 2020)
..